INTERNALISASI KARAKTER RELIGIUS SISWA MELALUI KEGIATAN EKSTRAKURIKULER DI SMPN 9 MALANG - Muhammad Zaini; Anwar Sa’dullah; Arief Ardiansyah (Vicratina : Jurnal Ilmiah Keagamaan, 2021)
SMP Negeri 9 Malang which has instilled religious values which are included in extracurricular activities, such as learning the Koran and prayer. The extracurricular activities of learning the Koran and prayer are not listed in the subject schedule but have an indirect influence on curricular activities. In this activity, students can learn the qur’an and prayer and develop other abilities. In this activity, students can practice their social and personal skills, outside of their daily academic mastery tasks, as well as their intra-curricular demands. Even further, students can train their social sensitivity, and practice various types of competencies that cannot be accommodated by academic activities. This study aims to (1) describe the condition of the religious character of students at SMP Negeri 9 Malang (2) to find out strategies for inculcating religious values through extracurricular activities in students at SMP Negeri 9 Malang. (3) identify the factors supporting and inhibiting the strategy of inculcating religious values through extracurricular activities in students at SMP Negeri 9 Malang